Alien species in Norway: Results from quantitative ecological impact assessments. Issue 1 (20th May 2020) - Sandvik, Hanno; Hilmo, Olga; Henriksen, Snorre; Elven, Reidar; Åsen, Per Arvid; Hegre, Hanne; Pedersen, Oddvar; Pedersen, Per Anker; Solstad, Heidi; Vandvik, Vigdis; Westergaard, Kristine B.; Ødegaard, Frode; et al.
Abstract: 1 . Due to globalisation, trade and transport, the spread of alien species is increasing dramatically. Some alien species become ecologically harmful by threatening native biota. This can lead to irreversible changes in local biodiversity and ecosystem functioning, and, ultimately, to biotic homogenisation. 2 . We risk‐assessed all alien plants, animals, fungi and algae, within certain delimitations, that are known to reproduce in Norway. Mainland Norway and the Arctic archipelago of Svalbard plus Jan Mayen were treated as separate assessment areas. Assessments followed the Generic Ecological Impact Assessment of Alien Species (GEIAA) protocol, which uses a fully quantitative set of criteria. 3 . A total of 1, 519 species were risk‐assessed, of which 1, 183 were species reproducing in mainland Norway. Among these, 9% were assessed to have a severe impact, 7% high impact, 7% potentially high impact, and 49% low impact, whereas 29% had no known impact. In Svalbard, 16 alien species were reproducing, one of which with a severe impact. 4 . The impact assessments also covered 319 so‐called door‐knockers, that is, species that are likely to establish in Norway within 50 years, and 12 regionally alien species. Of the door‐knockers, 8% and 10% were assessed to have a severe and high impact, respectively. 5 . The impact category of most species was driven by negative interactions with native species, transformation of threatened ecosystems, or genetic contamination. The proportion of alien species with high or severe impact varied significantly across the different pathways of introduction, taxonomic groups, time of introduction and the environments colonised, but not across continents of origin. 6 . Given the large number of alien species reproducing in Norway and the preponderance of species with low impact, it is neither realistic nor necessary to eradicate all of them. Our results can guide management authorities in two ways. First, the use of quantitative assessment criteria facilitates the prioritisation of management resources across species. Second, the background information collected for each species, such as introduction pathways, area of occupancy and ecosystems affected, helps designing appropriate management measures. Abstract : All alien species known to reproduce in Norway have been assessed for their ecological impact. The figure shows 16 of the 1183 species assessed, sorted according to their invasion potential and ecological effect. Abstract (Norwegian): 1 . Globalisering, handel og transport fører til en dramatisk økning i spredningen av fremmede arter. Noen fremmede arter er skadelige og truer det stedegne naturmangfoldet. Lokalt kan dette medføre irreversible endringer i det lokale biologiske mangfoldet og økosystemenes funksjon; globalt en homogenisering av artssammensetningen. 2 . Vi har gjennomført risikovurderinger av alle fremmede planter, dyr, sopper og alger som reproduserer i Norge og oppfyller visse avgrensninger. Svalbard og Jan Mayen ble behandla som et eget vurderingsområde, adskilt fra Fastlands‐Norge. Risikovurderingene ble gjort i tråd med GEIAA (Generic Ecological Impact Assessment of Alien Species), som benytter et rent kvantitativt kriteriesett. 3 . Totalt ble 1519 arter risikovurdert, hvorav 1183 reproduserte i Fastlands‐Norge. Av disse ble 9 % vurdert til å utgjøre en svært høy risiko, 7 % en høy risiko, 7 % en potensielt høy risiko, 49 % en lav risiko og 29 % ingen kjent risiko. På Svalbard forekom 16 reproduserende fremmede arter, hvorav én med svært høy risiko. 4 . Risikovurderingene omfatta også 319 såkalte dørstokkarter, dvs. fremmede arter som antas å kunne etablere seg i Norge innen 50 år, samt 12 regionalt fremmede arter. Blant dørstokkartene ble 8 % og 10 % vurdert til å utgjøre en svært høy respektive høy risiko. 5 . For de fleste arter ble risikokategorien bestemt av artenes interaksjoner med stedegne arter, tilstandsendringer i trua naturtyper eller genetisk forurensning. Andelen av fremmede arter med høy eller svært høy risiko varierte signifikant på tvers av ulike introduksjonsveier, artsgrupper, tidspunkt for introduksjon og koloniserte naturtyper, men ikke på tvers av opphavsområder. 6 . Gitt det store antallet av fremmede arter som reproduserer i Norge, og overvekten av arter som har lav risiko, er det verken realistisk eller nødvendig å utrydde alle. Resultatene våre kan hjelpe forvaltningsmyndighetene på to måter. For det første gjør bruken av kvantitative kriterier det lettere å prioritere ressurser på tvers av arter. For det andre kan passende forvaltningstiltak utarbeides på grunnlag av den innsamla bakgrunnsinformasjonen om artene, f.eks. deres spredningsveier, forekomstareal og berørte naturtyper.